Evaluation of Anomalous Coronary Arteries on 64 Slice Multidetector Computerized Tomographic Angiography - Tahir Naveed , Imran Saeed Ali , Syed Moazzam Ali Naqvi , Bilal S Mohydin , Muhammad Ayub, Tahir Naveed , Imran Saeed Ali , Syed Moazzam Ali Naqvi , Bilal S Mohydin , Muhammad Ayub (Journal of Rawalpindi Medical College, 2020)
Introduction: Anomalous Coronary arteries is a well-known congenital entity with variable effects. The majority of such patients are asymptomatic but some can have adverse effects like ischemia and arrhythmia. Its association with Sudden Cardiac Death in young is established. Objective: To determine the frequency of ACA on MDCT in patients referred for coronary artery disease assessment and to determine the origin, course, and morphological variable of SCD of ACA on MDCT. Materials and Methods: The study was done in the Department of Cardiovascular Imaging at the Punjab Institute of Cardiology. A retrospective data of patients undergoing CTA for CAD between a period of Jan 2009 and Dec 2017 were analyzed for the presence of Anomalous Coronary Artery (ACA). All patients having anomalous origin from opposite coronary cusp and its course were included. The patients with myocardial bridging and coronary artery fistula were excluded. Results: Total patients analyzed with MDCT for CAD and graft assessment between Jan 2009 and December 2017 were 8028. Fifty-three patients were excluded because of poor image quality. Among these ACA were found in 166 (2.08%). Gender distributions were 126 (75.9%) males and 40 (24.09%) females, the mean age in years was 49.31 ± 13.23. The most common ACA was Right coronary artery 83 followed by Left Circumflex 44 (26.50%), Left Anterior Descending Artery 22 (13.25%), and Left Main Stem 17 (10.24%) respectively. Fifty-three (31.92%) patients had previously unknown ACA and were found to have ACA on MDCT and 82 (49.39%) patients were referred following ICA for the confirmation of ACA. The Inter-arterial course was predominant in RCA and Left Coronary Artery 97% and 77% respectively. A retro artic course was predominant (100%) in LCx. Seven patients had associated cyanotic heart disease with ACA. Two patients(one LAD and one RCA) had origin from the Main Pulmonary artery. Conclusion: MDCT is the imaging modality of choice for the evaluation of ACA. It can identify the origin of ACA from opposite coronary cusp and defines the malignant course of ACA for the potential risk of sudden cardiac death.